Penerapan Kesantunan Berbahasa dalam Dakwah - F X Sarwadi; Wiwik Yulianti; Henry Yustanto; Bakdal Ginanjar; Chattri Sigit Widyastuti (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Language plays a crucial role not only as a means of communication but also as a reflection of the values and character of society. In the context of youth mosque da'wah, the use of polite language is crucial because it influences the effectiveness of conveying religious messages and shaping the morals of listeners. This study aims to examine the application of the principles of polite language in youth mosque da'wah in Karanganyar Regency and efforts to improve it through training activities. The method used was a qualitative approach with observation techniques, semi-structured interviews, and documentation. Data analysis was carried out in three stages: data reduction, data presentation, and drawing conclusions interactively. The results of the activity showed a significant increase in the participants' understanding and practice of polite language after attending the training. Based on the questionnaire results, participants' post-test scores increased compared to the pre-test, indicating the effectiveness of the training in strengthening their understanding of the concept of polite speech. Furthermore, observations of da'wah practices showed positive changes in the use of more polite, structured, and empathetic language. This activity not only improved participants' communication skills but also raised awareness of the importance of language ethics in da'wah. Thus, this language politeness training contributes to the character development of mosque youth, helping them become moral, communicative, and civilized young preachers. It is hoped that similar activities can be developed to a more advanced level in the future to strengthen the application of politeness in religious communication among youth.